Strong Coproximinality in Bochner $L^p$-Spaces and in Köthe Spaces (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we study strong coproximinality in Bochner $L^p$-spaces and in the Köthe Bochner function space $E(X)$. We investigate some conditions to be imposed on the subspace $G$ of the Banach space $X$ such that $L^{p}\left(μ,G \right)$ is strongly coproximinal in $L^{p}\left(μ,X \right), 1 ≤ p
Keywords: Strong Coapproximation; Bochner spaces; Köthe function space